Inclacumab Reduce Preexisting Red Blood Cell Adhesion to Activated Endothelial Cells: In-Vitro Assessment of the Microfluidic Platform Endothelium-on-a-Chip - Federici, Chiara; Spehn, Madelyn; Kovshovik, Pavel; Opheim, Kara; Combs, Gabrielle; Sertel, Seniye; Braxton, Samantha J; Bode, Allison; Zak, John; Geng, Xin; Gurkan, Umut A. (Blood, 2023)
Background: In 2019 FDA approved the use of an antibody anti P-selectin (Crizanlizumab) for the treatment of sickle cell disease (SCD) to reduce the vaso occlusive crisis (VOCs). New anti-adhesive treatments are being developed recently. Global Blood Therapeutics, Inc., acquired by Pfizer Inc. in October 2022, acquired Inclacumab from Roche and started two clinical trials now in phase 3 to evaluate the capacity of this humanized IgG4 monoclonal antibody anti P-selectin to reduce the VOCs in patients with SCD. In our recent work presented at EHA 23 in Frankfurt Germany, we showed that Inclacumab prevents the adhesion of RBCs to chronically and acutely heme activated human umbilical vein endothelial cells (HUVECs) with a statistically significant higher effect in comparison to Crizanlizumab. In this work we used a similar approach to test the capacity of Inclacumab in the reduction of preexisting adhesion events on acutely heme activated HUVECs. Methods:Whole blood EDTA samples from six SCD subjects all with HbSS genotypes were collected at University Hospital Cleveland Medical Center, Cleveland, OH, USA. To standardize the samples, we isolated RBCs by centrifugation and subsequential washes in Phospahte buffer s of the whole blood and resuspended in basal cell culture medium (EBM; Lonza, Morristown, NJ, USA) at a hematocrit of 20% with 10 mM of HEPES. HUVECs (Lonza, Morristown, NJ, USA) were introduced and maintained within the endothelialized microfluidic channels at physiological flow for at least 48-72 hours prior to experiments. We performed an acute short-term activation, where the blood samples were supplemented with 40 µM heme +/- 100 µg/ml injected through the microfluidic channels for 15 minutes, after the adhesion took place we washed the non-adherent cells with Inclacumab and Crizanlizumab and we compared with untreated washing buffer (both compounds were provided by Global Blood Therapeutics, Inc., a wholly owned subsidiary of Pfizer Inc. South San Francisco, CA, USA) A phase-contrast images of the remaining RBCs were acquired with an inverted microscope (DMi8 Leica Microsystems Inc. Deerfield, IL, USA) and quantified based on previous published methods (Figure 1A). Paired t-test was used to calculate statistical significance. Results: Acute short-term heme activation induces high level of RBCs adhesion. Both compounds Inclacumab and Crizanlizumab showed a reduction of the number of adherent RBCs to the activated heme, but only Inclacumab results statistically a significant higher reduction compared to untreated RBCs (Figure 1B). Conclusions: Inclacumab is able not only to prevent the adhesion of RBCs to acutely and chronically activated HUVECs but is able to remove the preexisting adhesion and results in significant higher reduction compared to untreated. RBCs adhesion assay on Endothelium-on-a-chip is a novel and efficient way to study the efficacy of the new antiadhesive drug and could be used to monitor patient response to new therapies in SCD. Figure1 : Effect of Inclacumab vs Crizanlizumab on removal of SCD RBC adhesion to heme activated HUVECs. A) Schematic of adhesion experiment and inverted microscope contrast of phase images 10X of adherent RBCs at acutely heme activated HUVECs. B) Inclacumab has statistically significant effect on remove adherent RBCs to acutely heme activated HUVECs (p=0.009, N=7) For all experiments, the heme concentrations were 40 µM and Inclacumab and Crizanlizumab were 100 µg/ml. Scale bare 20 µm. P-values were based on paired t-test. Error bars represent the standard error of the mean (SEM) Federici:BioChip Labs Inc.: Current Employment, Current holder of stock options in a privately-held company, Research Funding. Zak:BioChip Labs Inc: Current Employment, Current holder of stock options in a privately-held company; Xatek Inc: Current Employment, Current holder of stock options in a privately-held company. Geng:Pfizer Inc: Current Employment. Gurkan:BioChip Labs Inc: Current Employment, Current holder of stock options in a privately-held company, Patents & Royalties, Research Funding; DxNow Inc.: Current holder of stock options in a privately-held company, Patents & Royalties; Xatek Inc.: Current holder of stock options in a privately-held company, Patents & Royalties; Hemex Health Inc.: Current Employment, Current holder of stock options in a privately-held company, Patents & Royalties, Research Funding. [Display omitted]